2020
DOI: 10.1111/ejed.12389
|View full text |Cite
|
Sign up to set email alerts
|

Matching between students and universities: What are the sources of inequalities of access to higher education?

Abstract: It is assumed that a perfect balance between student academic achievement and university quality is beneficial both for students and higher education institutions (HEIs). Matching theory predicts the existence of perfect matching between the two groups in the absence of transaction costs associated with university enrollment. However, in this study we show cases of mismatch situations in Russia under the Unified State Exam (USE) -the standardized student admission mechanism. This research studies the reasons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
10
0
1
Order By: Relevance
“…Ситуацию, когда выпускники школ поступают в менее престижные университеты, чем позволяют их академические достижения, принято называть академическим несоответствием (academic undermatch) [Deutschlander, 2017]. Вуз, который не соответствует академической успеваемости абитуриента, как правило, выбирают именно представители семей с низким СЭС [Roksa, Deutsch lander, 2018;Prakhov, Sergienko, 2017]. На основе данных МЭо прослеживается аналогичная тенденция: респонденты с высшим образованием более позитивно оценива-ют образовательные возможности своих детей (рис.…”
Section: возможности которые открывает высшее образованиеunclassified
“…Ситуацию, когда выпускники школ поступают в менее престижные университеты, чем позволяют их академические достижения, принято называть академическим несоответствием (academic undermatch) [Deutschlander, 2017]. Вуз, который не соответствует академической успеваемости абитуриента, как правило, выбирают именно представители семей с низким СЭС [Roksa, Deutsch lander, 2018;Prakhov, Sergienko, 2017]. На основе данных МЭо прослеживается аналогичная тенденция: респонденты с высшим образованием более позитивно оценива-ют образовательные возможности своих детей (рис.…”
Section: возможности которые открывает высшее образованиеunclassified
“…In addition, individual USE results may be associated ('matched') with the type of university in which students enrol. There are studies that demonstrate favourable conditions for the perfect match between the quality of an applicant (his/her USE scores), and the quality of a university, calculated on the basis of the average USE score among admitted students (Prakhov & Sergienko, 2020). In turn, the quality of higher education (and higher education institution, or HEI) as a measure of investment in human capital after graduation can positively influence both expected (Prakhov, 2017) and actual salaries after graduation (Roshchin & Rudakov, 2016).…”
Section: The Analy Tic Al Fr Ame Work Of the S Tudy: The Model Of Smentioning
confidence: 99%
“…On the other hand, academic performance can itself be a function of individual, family and school characteristics (Prakhov, 2016a(Prakhov, , 2016bPrakhov & Sergienko, 2020). Thus, individual USE scores can be positively associated with student performance in secondary school, studying in schools with special status, in-depth study of | 307…”
Section: The Analy Tic Al Fr Ame Work Of the S Tudy: The Model Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the USE represents a unified set of requirements and procedures, but individual educational opportunities differ across regions and towns. Previous studies have shown that factors, in addition to individual student's abilities, namely family and school characteristics, play an important role in determining accessibility to higher education (Anikina et al 2014;Konstantinovskiy 2010;Prakhov 2016a;Prakhov, Sergienko 2020;Sá et al 2006). In the regional context, the problem of access to higher education can manifest itself even more strongly.…”
Section: Introductionmentioning
confidence: 99%